2016
DOI: 10.1186/s12942-016-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of health intervention programs and arsenic exposure on child mortality from acute lower respiratory infections in rural Bangladesh

Abstract: BackgroundRespiratory infections continue to be a public health threat, particularly to young children in developing countries. Understanding the geographic patterns of diseases and the role of potential risk factors can help improve future mitigation efforts. Toward this goal, this paper applies a spatial scan statistic combined with a zero-inflated negative-binomial regression to re-examine the impacts of a community-based treatment program on the geographic patterns of acute lower respiratory infection (ALR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…We found that some complex regression-based modeling approaches have been used to evaluate the joint effects of multiple stressors. For example, the combined effects of exposure to arsenic contamination in drinking water and health intervention programs on child mortality from acute lower respiratory infections were modeled by a zero-inflated negative binomial regression [54]. Both simple regression and Bayesian sparse spatial multilevel models were utilized to evaluate the relationship between lead exposure and both gonorrhea and chlamydia, accounting for other non-chemical stressors such as index of concentrated disadvantage [57].…”
Section: Resultsmentioning
confidence: 99%
“…We found that some complex regression-based modeling approaches have been used to evaluate the joint effects of multiple stressors. For example, the combined effects of exposure to arsenic contamination in drinking water and health intervention programs on child mortality from acute lower respiratory infections were modeled by a zero-inflated negative binomial regression [54]. Both simple regression and Bayesian sparse spatial multilevel models were utilized to evaluate the relationship between lead exposure and both gonorrhea and chlamydia, accounting for other non-chemical stressors such as index of concentrated disadvantage [57].…”
Section: Resultsmentioning
confidence: 99%
“…We found that some complex regression-based modeling approaches have been used to evaluate the joint effects of multiple stressors. For example, the combined effects of exposure to arsenic contamination in drinking water and health intervention programs on child mortality from acute lower respiratory infections were modeled by a zero-inflated negative binomial regression [56]. Both simple regression and Bayesian sparse spatial multilevel models were utilized to evaluate the relationship between lead exposure and both gonorrhea and chlamydia, accounting for other non-chemical stressors such as index of concentrated disadvantage [53].…”
Section: Methodsmentioning
confidence: 99%
“…Migrant location methods developed by Kuhn and Barham that took advantage of near-universal cell phone availability were extraordinarily successful: More than 92% of those alive in each targeted age/sex group responded to our survey. This is not the place for a full list of publications, but I mention a few studies of determinants of elder's survival (Kuhn et al 2006, Rahman et al 2004, childbearing and women's survival (Menken et al 2003), arsenic exposure and health ( Jochem et al 2016), and long-term effects of exposure to famine (Kagy 2015). Early evaluations of the MCH/FP intervention show it was associated with higher cognitive functioning (Barham 2012), less outmigration (Barham & Kuhn 2014 title their paper "Staying for Benefits"), lower family size and increased consumption and child education (Foster & Milusheva 2015), and better labor market outcomes (Barham et al 2016).…”
Section: Health and Population Change In Bangladesh-the Matlab Studiesmentioning
confidence: 99%